COMMITMENT TO INTERNATIONAL ACCREDITATION IN ISLAMIC-BASED UNIVERSITIES AFTER THE COVID-19 - Dedi Amrizal; Yusriati Yusriati (Proceeding International Seminar of Islamic Studies, 2022)
Commitment to international accreditation in higher education must be supported by three parties. First, there is a commitment from the rectorate; second, there is a commitment from the quality assurance team; and third, commitment from the accreditation team. The implementation of international accreditation means that it has received guaranteed funding and facility support from the university; the existence of technical and scientific support as well as basic training from the university's quality assurance team; as well as the existence of accrediting staff in study programs. The existence of international accreditation in the future will be a benchmark for success in realizing the vision, mission and statutes of higher education. International Accreditation must be an important aspect of realizing the commitment of a higher education targeting word class university. The purpose of this research is to explore the extent of commitment of Islamic-based universities in achieving international accreditation in their study programs and it aims to describe the readiness of Islamic-based universities and their study programs towards international accreditation after the Covid-19 Pandemic. Descriptive research method used with qualitative data processing. The results of this study indicate that the commitment built at Islamic-based universities is very low and the study programs are also still busy with independent learning curriculum activities and national accreditation.Keywords: Accreditation, International, International Accreditation, University and Commitment.